POLICY IMPLEMENTATION OF HALAL PRODUCT ASSURANCE FOR PHARMACEUTICAL PRODUCTS IN INDONESIA - Fadliyah, Hilyatul; Nurwahyuni, Atik (UI Scholars Hub, 2022)
After the implementation of halal product assurance (HPA) became a public policy, the assurance for halal pharmaceutical products is a must. However, the implementation has been relaxed for several years. This shows that the policy implementation is complicated. This study aimed to analyze and evaluate the implementation process of the HPA policy for pharmaceutical products in Indonesia. We applied Van Meter Van Horn’s theory using the qualitative method through in-depth interviews with eight informants and a review ten documents. The result shows that the implementation is going well but is still not optimal, especially from the point of view regarding halal certification for pharmaceutical products. The main obstacle for business actors in this implementation is obtaining halal raw materials because most of them are still imported. Moreover, a lack of massive socialization and education have also appeared. All stakeholders involved should improve performance according to their respective duties to implement better when the obligation has begun.